2009
DOI: 10.1515/mfir.2009.006
|View full text |Cite
|
Sign up to set email alerts
|

The Digitization of Historic Newspapers on Microfilm: The Kentucky Experience

Abstract: As the Kentucky representative in the National Digital Newspaper Program (NDNP), the University of Kentucky Libraries Preservation and Digital Programs (UKPDP) team has worked extensively with historic newspaper digitization from microfi lm over the last four years, using both an in-house production methodology and vendor resources. With more than 50 years experience with microfi lming newspapers added to that, UKPDP is well versed with issues related to historic newspapers on microfi lm. "Digitizing historic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…During the 1930s, librarians at Harvard and Yale Universities, the New York Public Library and the Library of Congress began to adopt a new technological solution to the challenge of preserving historic newspapers, the microfilm (Terry, 2009, p. 55). University of Kentucky librarian Kopana Terry (2009, p. 55) has observed that “polyester-based silverhalide microfilm is a proven preservation medium that can last up to 500 years under the right conditions.” Libraries and later commercial publishers began to microfilm historic newspapers especially nationally important newspapers such as the London Times , the New York Times and the Washington Post . By the early 1950s, the American Newspapers on Microfilm directory listed several thousand newspaper titles which had been microfilmed.…”
Section: Historic Newspapers As a Primary Source For Marketing Histor...mentioning
confidence: 99%
“…During the 1930s, librarians at Harvard and Yale Universities, the New York Public Library and the Library of Congress began to adopt a new technological solution to the challenge of preserving historic newspapers, the microfilm (Terry, 2009, p. 55). University of Kentucky librarian Kopana Terry (2009, p. 55) has observed that “polyester-based silverhalide microfilm is a proven preservation medium that can last up to 500 years under the right conditions.” Libraries and later commercial publishers began to microfilm historic newspapers especially nationally important newspapers such as the London Times , the New York Times and the Washington Post . By the early 1950s, the American Newspapers on Microfilm directory listed several thousand newspaper titles which had been microfilmed.…”
Section: Historic Newspapers As a Primary Source For Marketing Histor...mentioning
confidence: 99%
“…Razlučivost teksta na mikrofi lmu smatraju zadovoljavajućom. S druge strane, K. Terry (2009) sagledava novinske fotografi je kao sadržaj koji će mikrofi lmiranjem izgubiti na kvaliteti te zaključuje da neizbježno dolazi do manipulacije i promjene prilikom bilo kojeg preformatiranja, pri čemu je cilj da se manipulira što je manje moguće u odnosu na tzv. master sliku, bila ona analogna ili digitalna.…”
Section: Snimanja Novina U Svrhu Zaštite I Povećanja Dostupnostiunclassified